Strategic leaders driving innovation through digital transformation: an exploratory study in the South African trade, catering, and accommodation sector - Waugh, Beverley (University of Pretoria, 2026)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2025.